Tax Audit Analysis of Chicago Enterprise LTD in Preventing the Tax Lawsuit Strategies on Dispute The Notice of Tax Underpayment Assessment of Income Tax Article 21 in Tax Court of Jakarta - I P W R Pranata; N S Hardika; P D Hudiananingsih (Journal of Applied Sciences in Accounting, Finance, and Tax, 2018)
This study aims to analyze the process of tax audit of Chicago Enterprise, Ltd that raises Notice of Tax Underpayment Assessment of Income Tax Article 21 and to formulate appropriate and targeted strategies in winning a lawsuit in the Jakarta Tax Court. The data used are qualitative and quantitative data. Sources of data are primary and secondary data. Data collecting process used are observation, interview, and documentation. Researcher uses qualitative data analysis technique, whereas tax audit data was analyzed and compared with the tax law to prove the mal procedures on the investigations. The result of the research proves that Notice of Tax Underpayment Assessment Number 00003/201/15/525/2017 has violated the provisions of taxation such as PMK 184/PMK.03/2015 on Procedures of Inspection, where the examiner does not follow the rules and stages of investigations and ignore the rights of taxpayers that should be obtained in the process of investigation; PMK 183/PMK.03/2015 Procedures for Issuance of Tax Assessment Letter and Tax Claims, where SKPKB has been issued and delivered by courier when the taxpayer is still in the process of final discussion of investigation results in KPP Pratama Klaten; Instructions of the Director General of Taxation No. 12/PJ/2016 concerning the policy of issuance of instruction/approval/assignment and execution of inspection during the tax amnesty periode where KPP Pratama Klaten issues tax assessment in the period of tax amnesty and does not provide an opportunity for taxpayers to join the program. Because of that the company supplicates the judges to grant the lawsuit.